A panel analysis of Philippine banks’ loan portfolio quality in relation to their bank lending rates, bank performance, and key accounts - Coronel, Antonio Miguel Tayag (Animo Repository, 2021)
The main objective of the study was to determine the relationship of bank lending rates, performance and its key accounts to loan portfolio quality. The group measured Loan Portfolio Quality using the ratio of Non-Performing Loans over Total Loan Portfolio (NPL/TLP). The researchers collected data from the annual reports of 9 universal banks using a 10 year period going from 2010 to 2019 listed in the Philippine Stock Exchange. 13 variables were selected and the researchers hypothesized that each variable either had or did not have a significant relationship with loan portfolio quality. With the NPL ratio serving as a proxy for loan portfolio quality, the research utilized a fixed effects model to determine the effects of the independent variables on loan portfolio quality. The regression model found that 6 out 13 independent variables to be significant in determining a bank’s LPQ. These variables include bank lending rates (BLR), loan to deposit ratio (LDR), general loan loss provision (GLLP), specific loan loss provision (SLLP), real and other properties acquired (ROPA), and total loan portfolio (TLP). Furthermore, GLLP, SLLP, ROPA were found to have a positive or direct relationship with loan portfolio quality while BLR, LDR, and TLP have a negative or indirect relationship with loan portfolio quality.